Covert Speech Comprehension Predicts Recovery From Acute Unresponsive States. Issue 4 (9th January 2021) - Sokoliuk, Rodika; Degano, Giulio; Banellis, Leah; Melloni, Lucia; Hayton, Tom; Sturman, Steve; Veenith, Tonny; Yakoub, Kamal M.; Belli, Antonio; Noppeney, Uta; Cruse, Damian
Abstract : Objective: Patients with traumatic brain injury who fail to obey commands after sedation‐washout pose one of the most significant challenges for neurological prognostication. Reducing prognostic uncertainty will lead to more appropriate care decisions and ensure provision of limited rehabilitation resources to those most likely to benefit. Bedside markers of covert residual cognition, including speech comprehension, may reduce this uncertainty. Methods: We recruited 28 patients with acute traumatic brain injury who were 2 to 7 days sedation‐free and failed to obey commands. Patients heard streams of isochronous monosyllabic words that built meaningful phrases and sentences while their brain activity via electroencephalography (EEG) was recorded. In healthy individuals, EEG activity only synchronizes with the rhythm of phrases and sentences when listeners consciously comprehend the speech. This approach therefore provides a measure of residual speech comprehension in unresponsive patients. Results: Seventeen and 16 patients were available for assessment with the Glasgow Outcome Scale Extended (GOSE) at 3 months and 6 months, respectively. Outcome significantly correlated with the strength of patients' acute cortical tracking of phrases and sentences ( r > 0.6, p < 0.007), quantified by inter‐trial phase coherence. Linear regressions revealed that the strength of this comprehension response (beta = 0.603, p = 0.006) significantly improved the accuracy of prognoses relative to clinical characteristics alone (eg, Glasgow Coma Scale [GCS], computed tomography [CT] grade). Interpretation: A simple, passive, auditory EEG protocol improves prognostic accuracy in a critical period of clinical decision making. Unlike other approaches to probing covert cognition for prognostication, this approach is entirely passive and therefore less susceptible to cognitive deficits, increasing the number of patients who may benefit. ANN NEUROL 2021;89:646–656